Tunable Thermoelastic Anisotropy in Hybrid Bragg Stacks with Extreme Polymer Confinement. (4th December 2019) - Wang, Zuyuan; Rolle, Konrad; Schilling, Theresa; Hummel, Patrick; Philipp, Alexandra; Kopera, Bernd A. F.; Lechner, Anna M.; Retsch, Markus; Breu, Josef; Fytas, George
Abstract: Controlling thermomechanical anisotropy is important for emerging heat management applications such as thermal interface and electronic packaging materials. Whereas many studies report on thermal transport in anisotropic nanocomposite materials, a fundamental understanding of the interplay between mechanical and thermal properties is missing, due to the lack of measurements of direction‐dependent mechanical properties. In this work, exceptionally coherent and transparent hybrid Bragg stacks made of strictly alternating mica‐type nanosheets (synthetic hectorite) and polymer layers (polyvinylpyrrolidone) were fabricated at large scale. Distinct from ordinary nanocomposites, these stacks display long‐range periodicity, which is tunable down to angstrom precision. A large thermal transport anisotropy (up to 38) is consequently observed, with the high in‐plane thermal conductivity (up to 5.7 W m −1  K −1 ) exhibiting an effective medium behavior. The unique hybrid material combined with advanced characterization techniques allows correlating the full elastic tensors to the direction‐dependent thermal conductivities. We, therefore, provide a first analysis on how the direction‐dependent Young's and shear moduli influence the flow of heat. Abstract : Bragg‐Stapel aus alternierenden Hectorit‐ und Polyvinylpyrrolidon‐Schichten werden mit Ångström‐Präzision hergestellt. Über die Probenzusammensetzung lassen sich die mechanischen und thermischen Anisotropieverhältnisse steuern; sie erreichen Werte von bis zu 7 bzw. 38.